The capitalist state and development perspectives (Revista Innova Educación, 2019)
The purpose of this article was to analyze and interpret theoretical referents, articles, journals, repositories about the capitalist state and how it determines the perspectives of development of civil society that it represents. The methodology used was the exploratory documentary, which describes the succession of the capitalist state and the perspectives of development consisting of a systematic review of documents and bibliography, for the selection of sources and bibliographic analysis the bibliographic record was used. The results of the study present the opinions and discussion of researchers in relation to the capitalist state and its functions for sustainable social development. It is concluded that the capitalist state and the perspectives of development are optimal, although there are advantages and disadvantages.
Keywords: Capitalism; state; nation; development